Glass cloth composite material
The glass cloth composite material with carbon nanotube nonwoven fabric and thermosetting resin addresses the toughness and shielding limitations of existing materials, offering enhanced electromagnetic shielding and impact resistance for automotive and communication applications.
Patent Information
- Application Number
- JP2023102885
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-09
AI Technical Summary
Existing resin-impregnated glass cloth reinforced composite materials lack sufficient toughness and electromagnetic wave shielding properties, limiting their use in automotive applications, especially in autonomous vehicles, and existing carbon nanotube-based shielding materials are difficult to handle and have insufficient performance.
A glass cloth composite material comprising at least one layer of glass cloth and one layer of carbon nanotube nonwoven fabric, impregnated or laminated with a thermosetting resin, achieving a balanced ratio of glass cloth to carbon nanotube nonwoven fabric layers for improved impact resistance and electromagnetic shielding.
The composite material provides excellent electromagnetic wave shielding and impact resistance, making it suitable for lightweight, fuel-efficient vehicle structures and high-speed communication devices without the use of strong acidic compounds.
Smart Images

Figure 2025002595000001 
Figure 2025002595000002 
Figure 2025002595000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass cloth composite material, and in particular to a glass cloth composite material having electromagnetic wave shielding properties and excellent impact resistance, which is useful for high-speed communication devices that use millimeter waves or terahertz electromagnetic waves, lightweight vehicles aimed at reducing carbon dioxide emissions and improving fuel efficiency, connected cars, and the like. [Background technology]
[0002] Traditionally, fiber-reinforced composite materials, which consist of reinforcing fibers and a matrix resin, have been applied to many fields, such as aerospace, automobiles, railway vehicles, ships, civil engineering and construction, and sporting goods, because they are lightweight yet have excellent mechanical properties such as strength and rigidity, as well as heat resistance and corrosion resistance. In the automotive sector, with the advancement of electrification, there is a demand for fiber-reinforced composite materials that are both lighter in weight and more impact-resistant in order to further improve fuel efficiency.
[0003] In recent years, high-speed communications such as 5G and 6G that use millimeter and terahertz electromagnetic waves are being considered for practical use. Wireless devices that use electromagnetic waves for communication are increasing, and the ever-increasing electromagnetic waves pose the risk of electronic devices malfunctioning due to interference from electromagnetic waves from the surroundings, and the risk of information leakage due to electromagnetic waves emitted by the electronic devices themselves. In addition, in order to promote the rapid development of autonomous driving such as automobiles, it is necessary to properly transmit and receive electromagnetic waves in various electromagnetic environments from low-frequency electromagnetic waves to millimeter waves. Therefore, electromagnetic wave shielding has become an important technical issue, and there is a demand for electromagnetic wave shielding materials with excellent electromagnetic wave shielding performance against microwaves, millimeter waves, and terahertz waves. As the use of electromagnetic waves becomes more advanced, there is also a growing need for new functionality in electromagnetic wave shielding materials, such as thinner films, lighter weight, and larger areas.
[0004] In addition, resin-impregnated glass-cloth reinforced composite materials, which use glass cloth as the reinforcing fiber, are lighter than metals and have been considered as an alternative material to metals to improve the fuel efficiency of electric vehicles and other vehicles, and have already been put to practical use in some cases. However, resin-impregnated glass cloth reinforced composite materials are not as strong as metals and do not have electromagnetic wave shielding properties, so there are limitations to their use as body structural materials, especially in self-driving cars.
[0005] In addition to metal materials, many electromagnetic wave shielding technologies have been proposed using conductive polymers, dielectric oxides, etc., such as carbon black, graphene, and carbon nanotubes, as electromagnetic wave shielding materials. Among them, carbon nanotubes made of carbon are attracting attention as a promising electromagnetic wave shielding material. Electromagnetic wave shielding materials using carbon nanotubes include a paste material in which carbon nanotubes are dispersed in a resin (Patent Document 1) and a water-based paint in which carbon nanotubes are dispersed in an aqueous solution (Patent Document 2), but both are difficult to handle and do not have sufficient electromagnetic wave shielding performance to be practical.Since the carbon nanotubes used have a fine fiber structure, their specific surface area is large and they cannot be dispersed in large quantities in a resin, so electromagnetic wave shielding materials using carbon nanotubes also have insufficient electrical conductivity. In addition, there is an electromagnetic wave shielding material (Patent Document 3) that uses a carbon nanotube sheet formed by electrospinning, but it has problems such as low strength and difficulty in handling. An electromagnetic wave shielding material (Patent Document 4) has been disclosed in which a protonating agent such as hydronium ions or hydrochloric acid is added to a sheet of carbon nanotubes, and then ferromagnetic materials such as iron or cobalt are added to improve conductivity; however, the protonating agent is a strongly acidic compound, and handling it is problematic. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-144000 A [Patent Document 2] JP 2012-174833 A [Patent Document 3] JP 2008-218859 A [Patent Document 4] Patent No. 6182176 Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, an object of the present invention is to provide a glass cloth composite material which has both excellent electromagnetic wave shielding properties and impact resistance, and which is also easy to handle without using a strongly acidic compound such as a protonating agent. [Means for solving the problem]
[0008] Means of the Invention The present inventors have conducted extensive research to solve the above problems and have found that the following glass cloth composite material can achieve the above objects, thereby completing the present invention. That is, the present invention provides the following glass cloth composite material.
[0009] [1] A glass cloth composite material having at least one layer of glass cloth and at least one layer of carbon nanotube nonwoven fabric, A glass cloth composite material in which at least one layer of the glass cloth and the carbon nanotube nonwoven fabric in the glass cloth composite material is impregnated with a thermosetting resin or laminated with a thermosetting resin film. [2] At least one layer of thermosetting resin-containing glass cloth prepreg, which is formed by impregnating a glass cloth with a thermosetting resin or laminating a thermosetting resin film on the glass cloth; 1. A glass cloth composite material according to claim 1, comprising at least one layer of a thermosetting resin-containing carbon nanotube nonwoven fabric prepreg in which a carbon nanotube nonwoven fabric is impregnated with a thermosetting resin or laminated with a thermosetting resin film. [3] The glass cloth composite according to [2], wherein the ratio of [number of layers of thermosetting resin-containing glass cloth prepreg / number of layers of thermosetting resin-containing carbon nanotube nonwoven fabric prepreg] in the glass cloth composite is 0.1 to 5.0. [4] The glass cloth composite according to any one of [1] to [3], wherein the carbon nanotube nonwoven fabric is a nonwoven fabric made of multi-walled carbon nanotubes alone, single-walled carbon nanotubes alone, or a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes. [5] The glass cloth composite according to any one of [1] to [4], wherein the carbon nanotube nonwoven fabric is a carbon nanotube nonwoven fabric in which multi-walled carbon nanotubes and single-walled carbon nanotubes are laminated. [6] Carbon nanotube nonwoven fabric is less than 1mm thick and has a breathability of 0.5cm 3 / cm 2 The glass cloth composite according to any one of [1] to [5], having a specific resistance of 0.005 Ω·cm or less and a specific resistance of 0.005 Ω·s or less. Effect of the Invention
[0010] The glass cloth composite material of the present invention has both excellent electromagnetic wave shielding properties and impact resistance, and is easy to handle because it is a composite of a carbon nanotube nonwoven fabric and a glass cloth that does not use a strongly acidic compound such as a protonating agent. Therefore, the glass cloth composite material of the present invention is a useful material for high-speed communication devices that use electromagnetic waves in the high frequency band of millimeter waves or higher, and is also useful as a body structural material or an in-vehicle material that can reduce weight and improve fuel efficiency because the material itself is lightweight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. The glass cloth composite of the present invention has at least one layer of glass cloth and at least one layer of carbon nanotube nonwoven fabric, and at least one layer of the glass cloth and the carbon nanotube nonwoven fabric in the glass cloth composite is impregnated with a thermosetting resin or laminated with a thermosetting resin film.
[0012] <Glass cloth> The glass cloth used in the present invention is a fabric woven using glass fibers. The glass fibers are not particularly limited, but preferably contain at least 50% by mass to 100% by mass of SiO2, 0% by mass to 30% by mass of Al2O3, and 0% by mass to 30% by mass of CaO, and particularly preferably fibers made of at least one type of glass selected from the group consisting of T glass, D glass, E glass, NE glass, and quartz glass. Among these, the type of glass constituting the glass fibers is more preferably E glass from the viewpoint of versatility, and T glass and quartz glass from the viewpoint of high strength and low thermal expansion.
[0013] In the present invention, the composition ratio of metal oxides in T glass, D glass, E glass, NE glass and quartz glass is as follows. T glass is a glass having a composition containing 62% by mass to 65% by mass of SiO2, 20% by mass to 25% by mass of Al2O3, 0% by mass to 0.01% by mass of CaO, 10% by mass to 15% by mass of MgO, 0% by mass to 0.01% by mass of B2O3, and 0% by mass to 1% by mass of Na2O and K2O combined. D glass is a glass having a composition containing 72% to 76% by mass of SiO2, 0% to 5% by mass of Al2O3, 0% to 1% by mass of CaO, 0% to 1% by mass of MgO, 20% to 25% by mass of B2O3, and 3% to 5% by mass of Na2O and K2O combined. E-glass is a glass having a composition containing 52% to 56% by mass of SiO2, 12% to 16% by mass of Al2O3, 15% to 25% by mass of CaO, 0% to 6% by mass of MgO, 5% to 10% by mass of B2O3, and 0 to 0.8% by mass of Na2O and K2O combined. NE glass is glass having a composition containing 52% by mass to 56% by mass of SiO2, 10% by mass to 15% by mass of Al2O3, 0% by mass to 10% by mass of CaO, 0% by mass to 5% by mass of MgO, 15% by mass to 20% by mass of B2O3, 0% by mass to 1% by mass of Na2O and K2O combined, and 0.05% by mass to 5% by mass of TiO2. Silica glass is glass containing 99.0% to 100% by mass of SiO2.
[0014] The glass fiber is not particularly limited, but is preferably one having a longitudinal tensile strength of 30 N / 25 mm or more, more preferably 45 N / 25 mm or more, when made into a glass cloth. This makes it possible to obtain a prepreg having excellent dimensional stability and impact strength properties. The longitudinal tensile strength is a value measured by a constant-speed extension tensile tester for a glass cloth in accordance with JIS R3420. In the measurement of the longitudinal tensile strength, the term "longitudinal direction" refers to the warp (vertical) direction.
[0015] The thickness of the glass cloth is not particularly limited, but is preferably 10 to 200 μm, more preferably 10 to 140 μm, and further preferably 20 to 100 μm, which improves the impregnation of the resin composition into the glass cloth and allows for a thinner glass cloth.
[0016] The air permeability of the glass cloth is not particularly limited, but is preferably 1 to 80 cm 3 / cm 2 s is preferable, and 3 to 50 cm 3 / cm 2 It is particularly preferable that the air permeability is 1 cm 3 / cm 2 If the thickness is less than 80 cm s, the impregnation of the resin composition into the glass cloth is deteriorated. 3 / cm 2 If it exceeds s, the tensile strength may decrease or vary.
[0017] The glass cloth can be obtained by weaving warp and weft yarns using a loom known per se, followed by opening. Examples of the loom include a jet loom such as an air jet or water jet loom, a shuttle loom, and a rapier loom. Examples of the weaving method using the loom include a plain weave, a satin weave, a tanabae weave, and a twill weave. The weaving structure of the glass cloth is not particularly limited, but a plain weave structure is preferred because it is excellent in processability, such as strength, smoothness, and impregnation with a resin composition.
[0018] Examples of the opening treatment include opening by water flow pressure, opening by high-frequency vibration using a liquid as a medium, opening by pressure of a fluid having surface pressure, and opening by pressure using a roll. Among these opening treatments, it is preferable to use opening by water flow pressure or opening by high-frequency vibration using a liquid as a medium, since it causes variation in the yarn width after the opening treatment for each of the warp yarns and the weft yarns. In addition, by using a plurality of treatment methods in combination, the occurrence of defects in the appearance of the glass cloth, such as twisted weave, caused by the opening treatment can be suppressed.
[0019] <Carbon nanotube nonwoven fabric> The carbon nanotube nonwoven fabric used in the present invention is a fabric in which single-walled and / or multi-walled carbon nanotube fibers having a diameter of 50 nm or less and a length of 2 mm or less, preferably 10 to 500 μm, are entangled, and the thickness of the nonwoven fabric itself is preferably 1 mm or less. The carbon nanotube nonwoven fabric used in the present invention may be a fabric in which the carbon nanotube fibers are made of single-walled carbon nanotubes, multi-walled carbon nanotubes, or a mixture of single-walled carbon nanotubes and multi-walled carbon nanotubes. The carbon nanotube nonwoven fabric may also be a fabric in which multi-walled carbon nanotubes and single-walled carbon nanotubes are laminated. Furthermore, the carbon nanotube nonwoven fabric may be a fabric in which multi-walled carbon nanotube nonwoven fabric and single-walled carbon nanotube nonwoven fabric are laminated.
[0020] The carbon nanotube nonwoven fabric used in the present invention preferably has a basis weight of 1 to 1000 g / m 2 and more preferably 2 to 500 g / m 2 and more preferably 5 to 100 g / m 2 The weight of the carbon nanotube nonwoven fabric is 1g / m 2 When the carbon nanotube nonwoven fabric has a basis weight of 1000 g / m or more, the mechanical strength is high, and the impact resistance and electromagnetic wave shielding properties are excellent. 2 It is preferable for the thickness to be not more than this because it provides an excellent balance between electromagnetic wave shielding properties and flexibility.
[0021] To improve electrical conductivity, the air permeability is 0.5 cm 3 / cm 2 A highly conductive carbon nanotube nonwoven fabric having a specific resistance of 0.005 Ω·cm or less, preferably 0.003 Ω·cm or less, is preferred.
[0022] Carbon nanotube nonwoven fabric is made by entangling carbon nanotube fibers obtained by known methods, for example, carbon nanotube fibers spun in a plasma furnace using a hydrocarbon gas such as methane gas, or carbon nanotube fibers melted and spun through pores.
[0023] The air permeability can be adjusted by the entanglement of the carbon nanotube fibers, the thickness of the carbon nanotube nonwoven fabric, pressing the carbon nanotube nonwoven fabric, etc. In this specification, the air permeability is the value of the air permeability of the cloth measured in accordance with JIS R 3420 using a Frazier type tester. Air permeability is preferably 0.5 cm 3 / cm 2 ·s or less, preferably 0.1cm 3 / cm 2 s or less, more preferably 0.05 cm 3 / cm 2 A carbon nanotube nonwoven fabric having a thickness of .s or less is preferable because it has good electrical conductivity and excellent electromagnetic wave shielding performance over a wide range of frequencies (10 kHz to 300 GHz).
[0024] Examples of carbon nanotube nonwoven fabrics having the above-mentioned properties include the following commercially available products. (1) CNTM10 Tortech Thickness 32μm, breathability 0.04cm 3 / cm 2 ·s, specific resistance 2.22E-03(Ω·cm) (2) CNTM30 Tortech Thickness: 78μm, breathability: 0.01cm 3 / cm 2 ·s, specific resistance 1.51E-03(Ω·cm) (3) MIRALON (registered trademark) manufactured by Huntsman Thickness: 20μm, breathability: 0.05cm 3 / cm 2 ·s, specific resistance 3.5E-03(Ω·cm) (4) Single-walled carbon nanotube nonwoven fabric, manufactured by Meijo Nano Carbon Co., Ltd. Thickness 50μm, air permeability 0.01cm 3 / cm 2 ·s, specific resistance 1.82E-04(Ω·cm)
[0025] <Thermosetting resin> Examples of the thermosetting resin that serves as a binder for the glass cloth and / or carbon nanotube nonwoven fabric include thermosetting resins selected from the group consisting of epoxy resins, phenolic resins, allylated epoxy resins, allylated polyphenylene ether resins, maleimide resins, bismaleimide resins, cyanate resins, cyclopentadiene-styrene copolymer resins, silicone resins, acrylic resins, and polyester resins. Among them, the thermosetting resin used in the present invention is preferably at least one selected from the following epoxy resins, bismaleimide resins and cyanate ester resins.
[0026] A preferred example of the epoxy resin is an epoxy resin having two or more glycidyl groups in one molecule. Examples of epoxy resins that can be preferably used in the present invention include bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD type epoxy resins, and bisphenol S type epoxy resins; epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; polyfunctional epoxy resins; N,N,O-triglycidyl-m-aminophenol; N,N Examples of glycidyl amine type epoxy resins include N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N,N-diglycidylaniline, and N,N-diglycidyl-o-toluidine; resorcinol diglycidyl ether; and triglycidyl isocyanurate. These epoxy resins may be used alone or in combination.
[0027] When an epoxy resin is used as the thermosetting resin, it is preferable to use a curing agent for the epoxy resin in combination. As the curing agent for the epoxy resin, any curing agent that has a phenolic hydroxyl group or an amino group having active hydrogen and forms a crosslinked structure with the epoxy resin can be used. As the curing agent having a phenolic hydroxyl group, any structure of phenolic resin having a phenolic hydroxyl group can be used. As the curing agent having an amino group, an aromatic amine curing agent that can obtain an epoxy resin cured product with high heat resistance and high elasticity is preferable. Specific examples of such aromatic amine curing agents include 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-di-t-butyl-5, Examples of the aromatic amine curing agent include solid aromatic amine curing agents such as 5'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, etc.; 2,2'-diethyldiaminodiphenylmethane; diethyltoluenediamines such as 2,4-diethyl-6-methyl-m-phenylenediamine, 4,6-diethyl-2-methyl-m-phenylenediamine, etc.; and liquid aromatic amine curing agents such as 4,4'-methylenebis(N-methylaniline), 4,4'-methylenebis(N-ethylaniline), 4,4'-methylenebis(N-sec-butylaniline), N,N'-di-sec-butyl-p-phenylenediamine, etc., or a mixture of solid and liquid aromatic amine curing agents. Among these, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenylmethane, and 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane are particularly preferred.
[0028] The amount of the phenolic resin having a phenolic hydroxyl group is preferably 0.1 to 2.0, more preferably 0.2 to 1.8, and particularly preferably 0.4 to 1.5 molar equivalents of the phenolic hydroxyl group per 1 molar equivalent of the epoxy group contained in the epoxy resin. If the amount is less than 0.1, unreacted epoxy groups remain, which may cause a decrease in adhesion, and if it exceeds 2.0, unreacted phenolic hydroxyl groups remain, which may cause a decrease in strength during high-temperature storage. The amount of aromatic amine curing agent to be added is such that the equivalent of all amino groups in the aromatic amine curing agent is preferably 0.7 to 1.5, more preferably 0.7 to 1.2, still more preferably 0.7 to 1.1, and particularly preferably 0.85 to 1.05, per 1 molar equivalent of epoxy groups. If the amount is less than 0.7, unreacted epoxy groups will remain, which may result in a decrease in glass transition temperature or decreased adhesion, whereas if it exceeds 1.5, the cured product will become hard and brittle, and cracks may occur during reflow or temperature cycling. The epoxy resin curing agent may be used alone or in combination of two or more kinds.
[0029] As the bismaleimide resin, a bismaleimide resin represented by the following formula (1) or formula (2) is preferably used since it has excellent heat resistance, low elasticity, toughness, adhesiveness, and the like.
[0030] [ka] (In formula (1), A represents a hydrocarbon group derived from a dimer acid skeleton.) [ka] (In formula (2), B is independently a tetravalent organic group having a cyclic structure, X is independently a divalent hydrocarbon group having 6 to 200 carbon atoms, at least one of which is a hydrocarbon group derived from a dimer acid skeleton, and n is 1 to 100.)
[0031] Dimer acid is a liquid dibasic acid mainly composed of a dicarboxylic acid having 36 carbon atoms, which is produced by dimerization of unsaturated fatty acids having 18 carbon atoms, derived from natural products such as vegetable oils and fats. Dimer acids do not have a single skeleton, but have multiple structures, and there are several types of isomers. Representative dimer acids are classified as linear, monocyclic, aromatic, and polycyclic. In this specification, the dimer acid skeleton refers to a group derived from a dimer diamine having a structure in which the carboxy group of a dimer acid is replaced with a primary aminomethyl group, and the average structure of the hydrocarbon group derived from the dimer acid skeleton is -C. 36 H 70 It may be written as -.
[0032] A representative bismaleimide resin of the formula (1) is SLK-6895 (trade name) manufactured by Shin-Etsu Chemical Co., Ltd.
[0033] In formula (2), B independently represents a tetravalent organic group having a cyclic structure, and among these, any of the tetravalent organic groups represented by the following structural formulas is preferable. [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (2).)
[0034] In addition, in formula (2), X is independently a divalent hydrocarbon group having 6 to 200 carbon atoms, preferably 8 to 100, and more preferably 10 to 50. Among these, it is preferable that the divalent hydrocarbon group is a branched divalent hydrocarbon group in which one or more hydrogen atoms are substituted with an alkyl or alkenyl group having 6 to 200 carbon atoms, preferably 8 to 100, and more preferably 10 to 50 carbon atoms. The branched divalent hydrocarbon group may be either a saturated aliphatic hydrocarbon group or an unsaturated hydrocarbon group, and may have an alicyclic structure or an aromatic ring structure in the middle of the molecular chain. At least one of X in formula (2) is a hydrocarbon group derived from a dimer acid skeleton (e.g., -C 36 H 70 -).
[0035] In formula (2), n is 1 to 100, preferably 1 to 60, and more preferably 1 to 50. If n is too large, the solubility and flowability may decrease, and moldability such as lamination and impregnation may be poor.
[0036] A representative bismaleimide resin of the formula (2) is a bismaleimide resin of the formula (4) (SLK-3000; product name, manufactured by Shin-Etsu Chemical Co., Ltd.). [ka]
[0037] The bismaleimide resins of formula (1) and formula (2) may be used alone or in combination of two or more kinds. Representative bismaleimide resins include the above-mentioned SLK-6895 (manufactured by Shin-Etsu Chemical Co., Ltd.) and SLK-3000 (manufactured by Shin-Etsu Chemical Co., Ltd.), as well as the SLK-2000 series (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0038] The number average molecular weight (Mn) of the bismaleimide resin is preferably from 300 to 50,000, more preferably from 500 to 30,000, and further preferably from 600 to 10,000. The number average molecular weight (Mn) referred to in this specification refers to the number average molecular weight measured by GPC under the following conditions using polystyrene as the standard substance.
[0039] [GPC measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.35mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L TSKgel SuperHZ4000(4.6mmI.D.×15cm×1) TSKgel SuperHZ3000(4.6mmI.D.×15cm×1) TSKgel SuperHZ2000 (4.6mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 5 μL (0.2% by mass in THF solution)
[0040] When using bismaleimide resin as the thermosetting resin, it is preferable to use a reaction initiator of bismaleimide resin as a curing catalyst. The reaction initiator of bismaleimide resin is not particularly limited as long as it accelerates the crosslinking reaction, and examples thereof include ion catalysts such as imidazoles, organic phosphorus compounds, tertiary amines, quaternary ammonium salts, boron trifluoride amine complexes, organophosphines, and organophosphonium salts; organic peroxides such as diallyl peroxide, dialkyl peroxide, peroxide carbonate, and hydroperoxide; and radical polymerization initiators such as azoisobutyronitrile. Among these, organic peroxides are preferred, and examples of the organic peroxides include dicumyl peroxide, t-butyl peroxybenzoate, t-amyl peroxybenzoate, dibenzoyl peroxide, diuraloyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,1-di(t-butylperoxy)cyclohexane, di-t-butyl peroxide, and dibenzoyl peroxide. The reaction initiator is preferably blended in an amount of 0.05 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the bismaleimide resin. The reaction initiator may be used alone or in combination of two or more kinds.
[0041] The cyanate ester resin is a cyanate ester compound having two or more cyanate groups in one molecule. As the cyanate ester compound having two or more cyanate groups in one molecule, generally known compounds can be used, but a cyanate ester compound represented by the following formula (5) is preferred. [ka]
[0042] In formula (5), R 1 and R 2 each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; R 3 are each independently a divalent linking group selected from the group consisting of the following formulae, and p is a number from 0 to 10. [ka] (R in the formula 4 are each independently a hydrogen atom or a methyl group.
[0043] Specific examples of the cyanate ester resin include the following cyanate ester compounds: bis(4-cyanatophenyl)methane, bis(3-methyl-4-cyanatophenyl)methane, bis(3,5-dimethyl-4-cyanatophenyl)methane, 1,1-bis(4-cyanatophenyl)ethane, 2,2-bis(4-cyanatophenyl)propane, 1,3-dicyanatobenzene, 1,4-dicyanatobenzene, 2-tert-butyl-1,4-dicyanatobenzene, 2,4-dimethyl-1,3-dicyanatobenzene, 2,5-di-tert-butyl-1,4- Dicyanatobenzene, tetramethyl-1,4-dicyanatobenzene, 1,3,5-tricyanatobenzene, 2,2'-dicyanatobiphenyl, 4,4'-dicyanatobiphenyl, 3,3',5,5'-tetramethyl-4,4'-dicyanatobiphenyl, 1,3-dicyanatonaphthalene, 1,4-dicyanatonaphthalene, 1,5-dicyanatonaphthalene, 1,6-dicyanatonaphthalene, 1,8-dicyanatonaphthalene, 2,6-dicyanatonaphthalene, 2,7-dicyanatonaphthalene Talen, 1,3,6-tricyanatonaphthalene, bis(4-cyanatophenyl)ether, 4,4'-(1,3-phenylenediisopropylidene)diphenyl cyanate, bis(4-cyanatophenyl)thioether, tris(4-cyanato-phenyl)phosphine, bisphenol E type cyanate ester, phenol novolac type cyanate, cresol novolac type cyanate, bis(3-ethyl-4-cyanatophenyl)methane, bis(4-cyanatophenyl)sulfonate Examples of the cyanate ester include 1,1,1-tris(4-cyanatophenyl)ethane, 2,2-bis(4-cyanatophenyl)-1,1,1,3,3,3-hexafluoropropane, diallyl bisphenol A type cyanate ester, diallyl bisphenol F type cyanate ester, biphenyl aralkyl type cyanate ester, dicyclopentadiene novolac type cyanate, naphthalene ring-containing cyanate ester, aralkyl type cyanate ester, heterocyclic type cyanate ester, etc. These cyanate ester compounds can be used alone or in combination of two or more.Among them, preferred cyanate ester compounds are bis(4-cyanatophenyl)methane, bis(3-methyl-4-cyanatophenyl)methane, 1,1-bis(4-cyanatophenyl)ethane, and phenol novolac type cyanate esters. More preferred cyanate ester compounds are 1,1-bis(4-cyanatophenyl)ethane and phenol novolac type cyanate esters. The cyanate ester compounds may be used alone or in combination.
[0044] It is preferable that the viscosity of the cyanate ester compound is 300 Pa·s or less at room temperature, since this provides excellent flowability and excellent impregnation into glass cloth or carbon nanotube nonwoven fabric, and allows the compound to be easily cured uniformly. The viscosity of the cyanate ester compound is a value measured by a B-type rotational viscometer at room temperature (23 to 30° C.) according to the method described in JIS K7117-1:1999.
[0045] When a cyanate ester resin is used as the thermosetting resin, it is preferable to use a curing agent for the cyanate ester resin in combination, and the curing agent for the cyanate ester resin may be any curing agent that reacts with a cyanate ester compound, and generally known curing agents may be used, such as phenol-based curing agents. Examples of the phenol-based curing agent include phenol novolac resins, naphthalene ring-containing phenolic resins, aralkyl-type phenolic resins, triphenol alkane-type phenolic resins, biphenyl skeleton-containing aralkyl-type phenolic resins, biphenyl-type phenolic resins, alicyclic phenolic resins, heterocyclic phenolic resins, naphthalene ring-containing phenolic resins, resorcinol-type phenolic resins, allyl group-containing phenolic resins, bisphenol-type phenolic resins such as bisphenol A-type resins and bisphenol F-type resins. The curing agent for the cyanate ester resin may be used alone or in combination of two or more kinds. The amount of the phenol-based curing agent to be added is preferably 0.5 to 20 parts by mass, and more preferably 1 to 10 parts by mass, based on 100 parts by mass of the cyanate ester resin. In addition, a commonly known curing accelerator may be used in combination to accelerate the curing of the cyanate ester resin. Examples of the curing accelerator include phosphorus compounds, tertiary amine compounds, and imidazole compounds. The curing accelerator may be used alone or in combination of two or more. The amount of the curing accelerator is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5.5 parts by mass, based on 100 parts by mass of the cyanate ester resin.
[0046] <Glass cloth prepreg containing thermosetting resin> The thermosetting resin-containing glass cloth prepreg using the glass cloth composite material of the present invention is obtained by impregnating the above-mentioned thermosetting resin or laminating a thermosetting resin film on the above-mentioned glass cloth, and is preferably impregnated with at least one thermosetting resin selected from epoxy resins, bismaleimide resins, and cyanate ester resins, or laminated with at least one thermosetting resin film selected from epoxy resins, bismaleimide resins, and cyanate ester resins. At least one thermosetting resin selected from epoxy resins, bismaleimide resins, and cyanate ester resins is preferably contained in an amount of 10 to 200 parts by mass per 100 parts by mass of the glass cloth. The content of the glass cloth in the thermosetting resin-containing glass cloth prepreg is preferably 50% by mass or more, more preferably 60% by mass or more. The content of the thermosetting resin in the thermosetting resin-containing glass cloth prepreg is preferably 5 to 50% by mass, more preferably 10 to 40% by mass. The thermosetting resin-containing glass cloth prepreg may be produced by the method described below, or a commercially available prepreg may be used.
[0047] <Thermosetting resin-containing carbon nanotube nonwoven fabric prepreg> The thermosetting resin-containing carbon nanotube nonwoven fabric prepreg using the glass cloth composite of the present invention is obtained by impregnating the above-mentioned carbon nanotube nonwoven fabric with the above-mentioned thermosetting resin or laminating a thermosetting resin film, and is preferably impregnated with at least one thermosetting resin selected from epoxy resins, bismaleimide resins, and cyanate ester resins, or laminated with at least one thermosetting resin film selected from epoxy resins, bismaleimide resins, and cyanate ester resins. At least one thermosetting resin selected from epoxy resins, bismaleimide resins, and cyanate ester resins is preferably contained in an amount of 10 to 200 parts by mass per 100 parts by mass of the carbon nanotube nonwoven fabric. The content of the carbon nanotube nonwoven fabric in the thermosetting resin-containing carbon nanotube nonwoven fabric prepreg is preferably 50% by mass or more, more preferably 70% by mass or more. The content of the thermosetting resin in the thermosetting resin-containing carbon nanotube nonwoven fabric prepreg is preferably 5 to 50% by mass, more preferably 10 to 30% by mass. The thermosetting resin-containing carbon nanotube nonwoven fabric prepreg may be produced by the method described below, or a commercially available product may be used.
[0048] The glass cloth composite material of the present invention may further contain the following components as optional components. <Thermoplastic resin> In addition to the above-mentioned thermosetting resin, a thermoplastic resin may be impregnated into the glass cloth and / or the carbon nanotube nonwoven fabric, or a thermosetting resin film containing a thermoplastic resin may be laminated onto the glass cloth and / or the carbon nanotube nonwoven fabric. Representative examples of the thermoplastic resin include polyethylene, polypropylene, polyphenylene ether, polyether ether ketone, polyether ketone, polyether sulfone, and fluororesin. In particular, a solvent-soluble thermoplastic resin is preferable for impregnating the glass cloth or the carbon nanotube nonwoven fabric. When a thermoplastic resin is added, the amount is 0 to 50 parts by mass per 100 parts by mass of the thermosetting resin.
[0049] <Coupling Agent> In the present invention, a coupling agent can be used to improve the wetting and adhesive strength between the glass cloth or carbon nanotube nonwoven fabric and the resin.
[0050] Examples of the coupling agent include silane coupling agents and alkoxide compounds such as titanium and aluminum. Among them, silane coupling agents are preferred, and examples of preferred silane coupling agents include compounds represented by the general formula Y-Si-X3. Here, Y is an organic group having a functional group such as an amino group, an epoxy group, a hydroxyl group, a carboxyl group, a vinyl group, a methacryl group, or a mercapto group, and X is a hydrolyzable functional group such as an alkoxy group. Specific examples of coupling agents include γ-glycidoxypropyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-aminobenzyltriethoxysilane, and γ-aminophenyltriethoxysilane. The amount of such coupling agent used is suitably within the range of 0.5 to 20 parts by mass per 100 parts by mass of the thermosetting resin.
[0051] In addition, instead of using a coupling agent, in order to improve wettability with the thermosetting resin, the surface of the glass cloth or carbon nanotube fiber can be treated with a diluted solution of the thermosetting resin.
[0052] <Inorganic materials> By filling the gaps between the entangled fibers of the glass cloth or carbon nanotube nonwoven fabric that constitutes part of the present invention with a highly conductive inorganic material, such as inorganic powder, inorganic fiber, or metal particles, it is possible to further increase the electrical conductivity and improve the electromagnetic wave shielding performance in the frequency band of 10 to 300 GHz. Representative examples of inorganic powders include carbon black, carbon nanotubes, graphene, graphite, silica, zinc oxide, alumina, boron nitride, aluminum nitride, short carbon fibers, and short alumina fibers. Representative examples of metal particles include copper, iron, silver, and gold, and resin particles surface-coated with these metals may also be added.
[0053] To further increase the thermal conductivity of the carbon nanotube nonwoven fabric or glass cloth, inorganic particles or fibers such as silica, zinc oxide, alumina, boron nitride, aluminum nitride, short carbon fibers, short alumina fibers, quartz fibers, glass fibers, etc. can be used. By using these, the thermal conductivity of the carbon nanotube nonwoven fabric can be increased to 50 to 80 W / m K.
[0054] The particle size of the inorganic material is not particularly limited, but an average particle size of 0.5 μm to 30 μm is preferred from the standpoint of heat dissipation and electrical conductivity. The average particle size of the inorganic material is the D50 value measured by a laser diffraction method. Furthermore, when carbon nanotubes are used as the inorganic material, for example, the average diameter of the carbon nanotubes is preferably 0.5 nm or more, more preferably 1 nm or more, and preferably 15 nm or less, more preferably 10 nm or less. The average diameter is a value obtained by measuring the diameter (outer diameter) of 100 randomly selected carbon nanotubes using a transmission electron microscope.
[0055] The inorganic material may be directly sprayed onto the glass cloth or carbon nanotube nonwoven fabric, or the glass cloth or carbon nanotube nonwoven fabric may be impregnated with a thermosetting resin having the inorganic material dispersed therein. The inorganic material can be sprayed onto the glass cloth or carbon nanotube nonwoven fabric by any method, including, for example, packing the inorganic material into the glass cloth or carbon nanotube nonwoven fabric using a press or laminator, dispersing the inorganic material in any solvent, spraying the dispersion onto the glass cloth or carbon nanotube nonwoven fabric with a sprayer, and then drying and removing the solvent, or a combination of these methods. Any solvent can be used as the solvent for the dispersion liquid, but a highly volatile solvent is preferable, for example, water, alcohol such as ethanol and isopropyl alcohol, acetone, toluene, hydrocarbon-based solvents, silicone-based solvents, etc. The concentration of the dispersion liquid is preferably 0.1 to 100 parts by mass with respect to 100 parts by mass of the inorganic material.
[0056] When the inorganic material is fixed by scattering it on the glass cloth or carbon nanotube nonwoven fabric, the amount of the material to be fixed is preferably 0.01 to 100 parts by mass per 100 parts by mass of the glass cloth or carbon nanotube nonwoven fabric. When the inorganic material dispersed in the thermosetting resin is impregnated into a glass cloth or a carbon nanotube nonwoven fabric or laminated as a thermosetting resin film, the amount of the inorganic material dispersed therein is preferably 5 to 60 parts by mass, more preferably 10 to 50 parts by mass, per 100 parts by mass of the thermosetting resin.
[0057] <Manufacturing method> The glass cloth composite material of the present invention is A method of preparing a thermosetting resin-containing carbon nanotube nonwoven fabric prepreg impregnated with a thermosetting resin or laminated with a thermosetting resin film, and laminating the thermosetting resin-containing carbon nanotube nonwoven fabric prepreg and a glass cloth; A method of preparing a thermosetting resin-containing glass cloth prepreg impregnated with a thermosetting resin or laminated with a thermosetting resin film, and laminating the thermosetting resin glass cloth prepreg and a carbon nanotube nonwoven fabric, or a method of producing the thermosetting resin-containing glass cloth prepreg and the thermosetting resin-containing carbon nanotube nonwoven fabric prepreg, and laminating them. It can be manufactured in. Examples of methods for producing a thermosetting resin-containing glass cloth prepreg include a wet method in which a thermosetting resin is dissolved in a solvent to reduce its viscosity and then impregnated into a glass cloth, and a melt rolling method in which a thermosetting resin is heated to reduce its viscosity and then impregnated into a glass cloth. Methods for manufacturing thermosetting resin-containing carbon nanotube nonwoven fabric prepregs include a wet method in which the thermosetting resin is dissolved in a solvent to reduce its viscosity and then impregnated into the carbon nanotube nonwoven fabric, and a melt rolling method in which the thermosetting resin is heated to reduce its viscosity and then impregnated into the carbon nanotube nonwoven fabric. Alternatively, a thermosetting resin film may be prepared by converting a thermosetting resin varnish into a film using a coater or the like, and the thermosetting resin film may be laminated on both sides of a glass cloth or a carbon nanotube nonwoven fabric to form a prepreg.
[0058] In the wet method, a volatile solvent is preferably used as the solvent, and after impregnating a glass cloth or a carbon nanotube nonwoven fabric with a thermosetting resin, the solvent is removed to produce a prepreg impregnated with the uncured thermosetting resin. Examples of the solvent include anisole, cyclohexanone, tetralin, mesitylene, xylene, toluene, tetrahydrofuran (THF), dimethylformamide (DMF), dimethylsulfoxide (DMSO), acetonitrile, etc., but are not limited to these depending on the thermosetting resin. These may be used alone or in combination. The amount of the solvent is preferably 5 to 95% by mass. If the solvent remains in the prepreg, it may have a negative effect on molding and may cause problems such as a worsening of the working environment. For this reason, the amount of solvent remaining in the prepreg is 1% by mass or less, preferably 0.5% by mass or less. As a method for removing the solvent, depending on the boiling point of the solvent used, heat treatment at 80°C to 150°C for about 10 minutes to 1 hour is preferable, and the removal of the solvent can be easily achieved by this heat treatment.
[0059] The melt rolling method is advantageous in various respects, such as not requiring a process for removing the solvent, and the work efficiency is relatively good. In the melt rolling method, glass cloth or carbon nanotube nonwoven fabric is expanded to the required width with a bar or the like, and a film of thermosetting resin is placed on both sides or one side of it, laminated, and heated and pressurized to produce a prepreg impregnated with uncured thermosetting resin.
[0060] The glass cloth (thermosetting resin-containing glass cloth prepreg) and the carbon nanotube nonwoven fabric (thermosetting resin-containing carbon nanotube nonwoven fabric prepreg) may be laminated in any number and in any order as long as there is one layer of each. However, particularly when both the glass cloth and the carbon nanotube nonwoven fabric contain a thermosetting resin, the ratio of [number of layers of thermosetting resin-containing glass cloth prepreg / number of layers of thermosetting resin-containing carbon nanotube nonwoven fabric prepreg] in the glass cloth composite is preferably 0.1 to 5.0, and more preferably 1.0 to 3.0 in terms of electromagnetic wave shielding properties and impact properties.
[0061] A glass cloth composite material having a desired shape can be obtained by laminating a thermosetting resin-containing glass cloth prepreg (or glass cloth) and a thermosetting resin-containing carbon nanotube nonwoven fabric prepreg (or carbon nanotube nonwoven fabric) and molding the laminate by, for example, the following molding methods 1) to 4). 1) Press molding This method involves stacking prepregs in a mold and applying pressure while heating and hardening them, making it suitable for mass production. 2) Autoclave molding In this method, prepregs are laminated in a mold, covered with bagging film, the pressure is reduced, and pressure is applied in an autoclave to heat and harden the material. 3) Oven molding This method involves laminating prepregs on a mold, covering them with bagging film, reducing the pressure, and then heating and curing them under vacuum pressure. 4) Sheet wrap molding This method involves wrapping prepreg around a mandrel and taping it, then heating and curing it to remove the core.
[0062] The heat curing conditions in the above molding method are, for example, a temperature preferably in the range of 120 to 200° C., more preferably in the range of 140 to 180° C., and a time preferably in the range of 0.5 to 10, more preferably in the range of 1 to 5. The pressure conditions in the press molding are, for example, preferably in the range of 0.1 to 0.9 MPa, and more preferably in the range of 0.2 to 0.5 MPa.
[0063] The glass cloth composite material of the present invention can be processed by such a molding method to manufacture various parts. Since the glass cloth composite material of the present invention is lightweight and has excellent electromagnetic wave shielding properties and impact resistance, it can be used as vehicle bodies and structural members of automobiles, drones, ships, aircraft, etc. The glass cloth composite material of the present invention is also suitable as a member that requires electromagnetic wave shielding properties, such as storage containers for automobile batteries that generate electromagnetic waves, motor members, and DC / DC converter sealing materials. Furthermore, the glass cloth composite material of the present invention can also be used as a member or a container for communication devices that use high frequencies of millimeter waves or more and require electromagnetic wave shielding properties and heat resistance. Since the carbon nanotube nonwoven fabric easily generates heat when a voltage is applied across both ends, the glass cloth composite material of the present invention can be used as a heating element in a wide range of applications. EXAMPLES
[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass". The materials used in the examples and comparative examples of the present invention are as follows.
[0065] (1) Bismaleimide resin (A-1) Bismaleimide resin represented by the following formula (SLK-3000, manufactured by Shin-Etsu Chemical Co., Ltd., number average molecular weight 5200) [ka]
[0066] (A―2) Bismaleimide resin represented by the following formula (SLK-6895, manufactured by Shin-Etsu Chemical Co., Ltd., number average molecular weight 689) [ka]
[0067] (2) Epoxy resin (A-3) Epoxy resin (ZX-1059, manufactured by Nippon Steel Chemical & Material Co., Ltd., a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin)
[0068] <Preparation of resin film> Resin Film (1) 100 parts by mass of the bismaleimide resin (A-1) was mixed with 1 part by mass of a curing catalyst (dicumyl peroxide, trade name "Percumyl D", manufactured by NOF Corporation) to obtain a bismaleimide resin composition. Cyclohexanone solvent was added so that the content of this bismaleimide resin composition was 50% by mass, and a cyclohexanone solution (1) of the bismaleimide resin composition was obtained. The cyclohexanone solution (1) of the bismaleimide resin composition was applied to a release-treated PET film having a thickness of 38 μm with a roller coater, and dried at 100° C. for 10 minutes to prepare an uncured resin film (1) having a thickness of 30 μm. Resin Film (2) 100 parts by mass of a bismaleimide resin composition containing 100 parts by mass of bismaleimide resin (A-2) and 1 part by mass of a curing catalyst (dicumyl peroxide, trade name "Percumyl D", manufactured by NOF Corporation) was added with 5 parts by mass of carbon nanotube powder ZEONANO SG101 (manufactured by Zeon Nano Technology Co., Ltd.), and mixed for 5 minutes at 2000 rpm using a planetary mixer to obtain a bismaleimide resin composition. Cyclohexanone solvent was added so that the content of this bismaleimide resin composition was 50% by mass, and a cyclohexanone solution (2) of the bismaleimide resin composition was obtained. The mixture was applied to a release-treated PET film having a thickness of 38 μm using a roller coater, and dried at 100 ° C for 10 minutes to prepare an uncured resin film (2) having a thickness of 30 μm. Resin Film (3) An epoxy resin composition was prepared by mixing 100 parts by mass of epoxy resin (A-3) and 38.3 parts by mass of aromatic amine curing agent (Kayahard AA, manufactured by Nippon Kayaku Co., Ltd.) (an amount such that the total equivalent of amino groups in the aromatic amine curing agent is 1.0 relative to 1 molar equivalent of epoxy groups contained in the epoxy resin). Toluene was added so that the content of this epoxy resin composition was 50% by mass, and a toluene solution of the epoxy resin composition (1) was obtained.
[0069] <Glass cloth> A plain weave fabric of glass fibers as specified in JIS R3413 was used. Glass Cloth (1) Using T-glass yarn (IPC name: E225), warp density (strands / 25mm) 60 strands / 25mm, weft density (strands / 25mm) 58 strands / 25mm, thickness 95μm, weight 104g / m 2 The glass cloth (1) was manufactured. Glass Cloth (2) Using T-glass yarn (IPC name: D450), warp density (threads / 25mm) 60 threads / 25mm, weft density (threads / 25mm) 60 threads / 25mm, thickness 50μm, weight 54g / m 2 The glass cloth (2) was manufactured. Glass Cloth(3) Made of quartz glass yarn (IPC name: E225), warp density (strands / 25mm) 60 strands / 25mm, weft density (strands / 25mm) 58 strands / 25mm, thickness 86μm, weight 85.5g / m 2 The glass cloth (3) was manufactured.
[0070] <Glass cloth prepreg> [Reference example 1] A 30 μm thick resin film (1) weighing 0.3 g cut to a 10 cm × 10 cm size was placed on each side of 1.04 g of glass cloth (1) measuring 10 cm × 10 cm and 95 μm thick, and laminated at 80° C. for 1 minute and then pressed at 150° C. for 15 minutes to prepare a prepreg (GC1) using the glass cloth.
[0071] [Reference example 2] A prepreg (GC2) using glass cloth was prepared in the same manner as in Reference Example 1, except that 0.54 g of glass cloth (2) having a thickness of 50 μm and a size of 10 cm×10 cm was used instead of the glass cloth (1).
[0072] [Reference example 3] A prepreg (GC3) using glass cloth was prepared in the same manner as in Reference Example 1, except that 0.86 g of glass cloth (3) having a thickness of 86 μm and a size of 10 cm×10 cm was used instead of the glass cloth (1).
[0073] <Carbon nanotube nonwoven fabric> Nonwoven fabric (1) CNTM30 (Tortech: multi-walled carbon nanotubes) Thickness: 78μm Breathability: 0.01cm 3 / cm 2 ·s Specific resistance: 1.51E-03 (Ω cm) Nonwoven fabric (2) CNTM10 (Tortech: multi-walled carbon nanotubes) Thickness: 32μm Breathability: 0.04cm 3 / cm2 ·s Specific resistance: 2.22E-03 (Ω cm) Nonwoven fabric (3) Single-walled carbon nanotube nonwoven fabric (manufactured by Meijo Nano Carbon Co., Ltd.) Thickness: 50μm Breathability: 0.01cm 3 / cm 2 ·s Specific resistance: 1.82E-04 (Ω cm) Nonwoven Fabrics(4) 1 g of single-walled carbon nanotube powder (ZEONANO SG101, Zeon Nano Technology Co., Ltd., average diameter: 3 nm) was sprinkled on both sides of 0.3 g of CNTM30 (nonwoven fabric (1)) to obtain carbon nanotube nonwoven fabric (4). The amount of single-walled carbon nanotube powder immobilized per 0.3 g of CNTM30 was 0.03 g. Thickness: 72μm Breathability: 0.01cm 3 / cm 2 ·s Specific resistance: 3.0E-03 (Ω cm) Nonwoven Fabrics(5) 0.3 g of CNTM30 (nonwoven fabric (1)) was immersed in 20 g of a solution containing 0.2 wt % single-walled carbon nanotubes (EC1.5P (NMP solution), manufactured by Meijo Nano Carbon Co., Ltd.) at 25°C for 30 minutes and dried at 200°C for 5 minutes to prepare a carbon nanotube nonwoven fabric (5) composed of single-walled carbon nanotubes and multi-walled carbon nanotubes. Thickness: 75μm Breathability: 0.02cm 3 / cm 2 ·s Specific resistance: 2.4E-03 (Ω cm)
[0074] <Carbon nanotube nonwoven fabric prepreg> [Reference example 4] A 30 μm thick, 0.3 g weight resin film (1) cut to a 10 cm × 10 cm size was placed on each side of 0.23 g of a 78 μm thick, 10 cm × 10 cm carbon nanotube nonwoven fabric (1), laminated at 80°C for 1 minute, and then pressed at 150°C for 15 minutes to prepare a prepreg (CNT1) using the carbon nanotube nonwoven fabric.
[0075] [Reference example 5] A prepreg (CNT2) using carbon nanotube nonwoven fabric was prepared in the same manner as in Reference Example 4, except that 0.10 g of carbon nanotube nonwoven fabric (2) having a thickness of 32 μm and a size of 10 cm × 10 cm was used instead of carbon nanotube nonwoven fabric (1).
[0076] [Reference example 6] A prepreg (CNT3) using carbon nanotube nonwoven fabric was prepared in the same manner as in Reference Example 4, except that 1.5 g of carbon nanotube nonwoven fabric (3) having a thickness of 50 μm and a size of 10 cm × 10 cm was used instead of carbon nanotube nonwoven fabric (1).
[0077] [Reference example 7] A prepreg (CNT4) using carbon nanotube nonwoven fabric was prepared in the same manner as in Reference Example 4, except that 0.22 g of carbon nanotube nonwoven fabric (4) having a thickness of 72 μm and a size of 10 cm × 10 cm was used instead of carbon nanotube nonwoven fabric (1).
[0078] [Reference example 8] A prepreg (CNT5) using carbon nanotube nonwoven fabric was prepared in the same manner as in Reference Example 4, except that 0.23 g of carbon nanotube nonwoven fabric (5) having a thickness of 75 μm and a size of 10 cm × 10 cm was used instead of carbon nanotube nonwoven fabric (1).
[0079] [Reference example 9] A prepreg (CNT6) using a carbon nanotube nonwoven fabric was prepared in the same manner as in Reference Example 4, except that the resin film (2) was used instead of the resin film (1).
[0080] [Reference example 10] A carbon nanotube nonwoven fabric (1) was impregnated with the toluene solution (1) of the epoxy resin composition prepared above and dried at 120° C. for 30 minutes to prepare a prepreg (CNT7) using the carbon nanotube nonwoven fabric.
[0081] For the prepregs CNT1 to 7 using the carbon nanotube nonwoven fabric, the thickness was measured with a micrometer, and the apparent resistivity was measured with an eddy current resistance measuring device (manufactured by NAPSON Co., Ltd.). The results are shown in Table 1. [Table 1]
[0082] The properties of the sheets produced in the examples and comparative examples were measured and evaluated by the following methods. The results are shown in Tables 2 and 3. Thickness: The thickness of the sheets was measured with a micrometer. Resistivity: The resistivity of the sheet was measured using an eddy current resistance measuring device (manufactured by NAPSON).
[0083] Electromagnetic wave shielding properties The electromagnetic shielding characteristic (SE) is defined by the following equation:
number
[0084] Impact strength The impact strength was measured by a puncture impact test in accordance with JIS K7211. First, two layers of the glass cloth prepreg (1) were laminated and heat-cured at 200° C. for 30 minutes to prepare a cured product of the glass cloth prepreg (1) having a thickness of 400 μm. The impact test value I of the cured product of the glass cloth prepreg (1) was measured. Subsequently, the impact test value II of each sheet produced in the examples or comparative examples was measured. From the impact test values I and II, the strength ratio of the impact test values was calculated as impact test value II / impact test value I.
[0085] [Example 1] One sheet of the glass cloth prepreg (GC1) produced in Reference Example 1 was placed on each of the upper and lower surfaces of the carbon nanotube nonwoven fabric prepreg (CNT1) produced in Reference Example 4, laminated into three layers, and pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a three-layer glass cloth composite (glass cloth composite sheet 1). The electromagnetic wave shielding properties and impact test strength ratio of this glass cloth composite sheet 1 are shown in Table 2.
[0086] [Example 2] One sheet of carbon nanotube nonwoven prepreg (CNT1) from Reference Example 4 was placed on each of the upper and lower surfaces of the glass cloth prepreg (GC1) from Reference Example 1 to form three layers, and then one more sheet of glass cloth prepreg (GC1) was placed on each of the uppermost and lowermost surfaces of the three layers to form five layers. The resulting mixture was then pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a five-layer glass cloth composite (glass cloth composite sheet 2). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratio of the glass cloth composite sheet 2.
[0087] [Example 3] A sheet of the carbon nanotube nonwoven prepreg (CNT1) prepared in Reference Example 4 was placed on the upper surface of the glass cloth prepreg (GC1), laminated into two layers, and pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a two-layer glass cloth composite (glass cloth composite sheet 3). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratio of the glass cloth composite sheet 3.
[0088] [Example 4] One sheet of carbon nanotube nonwoven prepreg (CNT1) from Reference Example 4 was placed on each of the upper and lower surfaces of the glass cloth prepreg (GC1) from Reference Example 1, laminated into three layers, and pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a three-layer glass cloth composite (glass cloth composite sheet 4). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratio of the glass cloth composite sheet 4.
[0089] [Example 5] One sheet of the glass cloth prepreg (GC2) of Reference Example 2 was placed on each of the upper and lower surfaces of the carbon nanotube nonwoven fabric prepreg (CNT1) of Reference Example 4, laminated into three layers, and pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a three-layer glass cloth composite (glass cloth composite sheet 5). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratio of the glass cloth composite sheet 5.
[0090] [Example 6] One sheet of the glass cloth prepreg (GC3) of Reference Example 3 was placed on each of the upper and lower surfaces of the carbon nanotube nonwoven fabric prepreg (CNT1) of Reference Example 4, laminated into three layers, and pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a three-layer glass cloth composite (glass cloth composite sheet 6). The electromagnetic wave shielding properties and impact test strength ratio of glass cloth composite sheet 6 are shown in Table 2.
[0091] [Example 7] One sheet of the glass cloth prepreg (GC1) from Reference Example 1 was placed on each of the upper and lower surfaces of the carbon nanotube nonwoven fabric prepreg (CNT2) produced in Reference Example 5, stacked into three layers, and pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a three-layer glass cloth composite (glass cloth composite sheet 7). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratio of the glass cloth composite sheet 7.
[0092] [Example 8] As in Example 1, one sheet of the glass cloth prepreg (GC1) from Reference Example 1 was placed on each of the upper and lower surfaces of the carbon nanotube nonwoven fabric prepreg (CNT3) produced in Reference Example 6, laminated into three layers, and pressed at a pressure of 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a three-layer glass cloth composite (glass cloth composite sheet 8). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratio of the glass cloth composite sheet 8.
[0093] [Examples 9 to 12] The carbon nanotube nonwoven prepregs (CNT4 to CNT7) produced in Reference Examples 7 to 10 were used instead of the carbon nanotube nonwoven prepreg (CNT1) produced in Reference Example 4, and the same procedure was followed as in Example 1, except that the carbon nanotube nonwoven prepregs were pressed at 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain three-layer glass cloth composites (glass cloth composite sheets 9 to 12). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratios of glass cloth composite sheets 9 to 12.
[0094] [Example 13] A sheet of carbon nanotube nonwoven fabric (1) was placed on the upper surface of the glass cloth prepreg (GC1), laminated into two layers, and pressed at 7.0 MPa in a heated press set at a temperature of 200°C and cured for 30 minutes to obtain a two-layer glass cloth composite (glass cloth composite sheet 13). Table 2 shows the electromagnetic wave shielding properties and impact test strength ratio of the glass cloth composite sheet 13.
[0095] [Comparative Example 1] The carbon nanotube nonwoven fabric prepreg (CNT1) produced in Reference Example 4 was heat cured at 200° C. for 30 minutes to produce a sheet-like cured product (Sheet 14) having a thickness of 135 μm. The electromagnetic wave shielding properties and impact test strength ratio of sheet 14 are shown in Table 3.
[0096] [Comparative Example 2] The carbon nanotube nonwoven fabric prepreg (CNT1) produced in Reference Example 4 was laminated in two layers and heat cured at 200° C. for 30 minutes to produce a sheet-like cured product (Sheet 15) having a thickness of 270 μm. The electromagnetic wave shielding properties and impact test strength ratio of Sheet 15 are shown in Table 3.
[0097] [Comparative Example 3] The carbon nanotube nonwoven fabric (1) was used as a sheet 16. The electromagnetic wave shielding properties and impact test strength ratio of sheet 16 are shown in Table 3.
[0098] [Comparative Example 4] The carbon nanotube nonwoven fabric (2) was used as a sheet 17. The electromagnetic wave shielding properties and impact test strength ratio of Sheet 17 are shown in Table 3.
[0099] [Table 2]
[0100] [Table 3]
[0101] As shown in Examples 1 to 13, the glass cloth composite sheet having a single layer of carbon nanotube nonwoven fabric prepreg had an impact test strength ratio of more than 1.0 compared to the sheet made of carbon nanotube nonwoven fabric prepreg of Comparative Example 1, and also when the glass cloth composite sheets having two layers of carbon nanotube nonwoven fabric prepreg of Examples 2 and 4 were compared to the sheet of Comparative Example 2, the impact test strength ratio was also more than 1.0, making it clear that the glass cloth composite sheet has excellent impact resistance. Furthermore, the glass cloth composite sheets of Examples 1 to 13 had electromagnetic wave shielding properties at 10 GHz that were equal to or better than those of Comparative Examples 1 and 2. The glass cloth composite of the present invention is a sheet that has no electromagnetic wave shielding effect when used alone as glass cloth, but by combining it with carbon nanotube nonwoven fabric, it becomes a highly reliable electromagnetic wave shielding sheet that retains electromagnetic wave shielding properties and has improved impact strength. [Industrial Applicability]
[0102] INDUSTRIAL APPLICABILITY The glass cloth composite material of the present invention has excellent electromagnetic wave shielding properties and strength, and therefore can be suitably used in devices compatible with high-speed, large-capacity communication and in-vehicle applications.
Claims
1. A glass cloth composite material having at least one layer of glass cloth and at least one layer of carbon nanotube nonwoven fabric, A glass cloth composite material, in which at least one layer of the glass cloth and the carbon nanotube nonwoven fabric in the glass cloth composite material is impregnated with a thermosetting resin or laminated with a thermosetting resin film.
2. At least one layer of a thermosetting resin-containing glass cloth prepreg obtained by impregnating a glass cloth with a thermosetting resin or laminating a thermosetting resin film on the glass cloth; 2. The glass cloth composite material according to claim 1, comprising at least one layer of a thermosetting resin-containing carbon nanotube nonwoven fabric prepreg in which a carbon nanotube nonwoven fabric is impregnated with a thermosetting resin or laminated with a thermosetting resin film.
3. The glass cloth composite according to claim 2, wherein the ratio of the number of layers of the thermosetting resin-containing glass cloth prepreg to the number of layers of the thermosetting resin-containing carbon nanotube nonwoven fabric prepreg in the glass cloth composite is 0.1 to 5.
0.
4. 2. The glass cloth composite material according to claim 1, wherein the carbon nanotube nonwoven fabric is a nonwoven fabric made of multi-walled carbon nanotubes alone, single-walled carbon nanotubes alone, or a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes.
5. 2. The glass cloth composite material according to claim 1, wherein the carbon nanotube nonwoven fabric is a carbon nanotube nonwoven fabric in which multi-walled carbon nanotubes and single-walled carbon nanotubes are laminated.
6. Carbon nanotube nonwoven fabric is less than 1mm thick and has a breathability of 0.5cm 3 / cm 2 2. The glass cloth composite material according to claim 1, having a surface roughness of 0.025 Ω·s or less and a specific resistance of 0.005 Ω·cm or less.
Citation Information
Patent Citations
Structural core
JP2015502465A
Surface material for composite structures
JP2018538172A
Method for producing the complex
JP2022518347A
Fabrication of fire retardant materials with nanoadditives
US20090148637A1
Screening method of resin molded semiconductor element
JP1986082176A